Pengenalan Olahan Herbal Daun Sirsak (Annona muricata L.) Untuk Membantu Pengobatan Penyakit Neoplasma - Yelfi Anwar; Alifvia Nurcahyani; Rina Pebriani; Hallimah Vira Maulida; Muhyiddin Al Firmansyah; Eka Kristina; Gabriel Janiva (Jurnal Kabar Masyarakat, 2024)
Soursop leaves have long been used as a traditional medicine that can inhibit the potential of cancer cells. The purpose of introducing herbal preparations of soursop leaves is to educate in the treatment of cancer or tumors using soursop leaves and to find out the content contained in soursop leaves. To make this soursop leaf preparation by boiling the boiled water will be used as herbal preparations. The method of implementing the introduction of soursop leaf preparations was carried out using a zoom meeting. The activity was accompanied by giving pre-test and post-test questionnaires with an average understanding of the pre-test percentage of 88% to 89.2% during the post test. From these results, it can be said that the webinar that has been carried out can provide benefits in the form of insight and knowledge to the community.